Evaluating Market Consolidation in Mobile Communications - Christos Genakos; Tommaso M. Valletti; Frank Verboven (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the dual relationship between market structure and prices and between market structure and investment in mobile telecommunications. Using a uniquely constructed panel of mobile operators' prices and accounting information across 33 OECD countries between 2002 and 2014, we document that more concentrated markets lead to higher end user prices. Furthermore, they also lead to higher investment per mobile operator, though the impact on total investment is not conclusive. Our findings are not only relevant for the current consolidation wave in the telecommunications industry. More generally, they stress that competition and regulatory authorities should take seriously the potential trade-off between market power effects and efficiency gains stemming from agreements between firms.
Keywords: K20; L10; L40; L96; 330; mobile telecommunications; market structure; prices; investments; mergers